Digital Work Culture in the Era of Society 5.0: An Observational Case Study in the Higher Education Administrative Environment - Simbolon, Dedi Holden (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study investigates the digital work culture within the administrative environment of Universitas Quality through an observational case study on the implementation of integrated systems including Q‑Enterprise, Q‑Layanan, Q‑Skripsi, Q‑Kinerja, Q‑Course, and Q‑Tracer. The findings indicate that these digital systems have significantly enhanced efficiency, transparency, and accountability in administrative workflows. However, challenges persist, particularly in the form of cultural resistance, limited two-way interaction, and low levels of engagement in self-directed learning. These findings highlight the critical importance of inclusive digital leadership, cross-generational digital literacy development, and reflective, data-driven evaluation mechanisms. The study recommends the advancement of adaptive and human-centered digital systems to support the transformation of organizational work culture in the context of Society 5.0.